Medical and biomedical research productivity from the Kingdom of Saudi Arabia (2008-2012) - Rabia Latif (Wolters Kluwer Medknow Publications, 2015)
Background: Biomedical publications from a country mirror the standard of Medical Education and practice in that country. It is important that the performance of the health profession is occasionally documented. Aims: This study aimed to analyze the quantity and quality of biomedical publications from the Kingdom of Saudi Arabia (KSA) in international journals indexed in PubMed between 2008 and 2012. Materials and Methods: PubMed was searched for publications associated with KSA from 2008 to 2012. The search was limited to medical and biomedical subjects. Results were saved in a text file and later checked carefully to exclude false positive errors. The quality of the publication was assessed using Journal Citation Report 2012. Results: Biomedical research production in KSA in those 5 years showed a clear linear progression. Riyadh was the main hub of medical and biomedical research activity. Most of the publications (40.9%) originated from King Saud University (KSU). About half of the articles were published in journals with an Impact Factor (IF) of < 1, one-fourth in journals with no IF, and the remaining one-fourth in journals with a high IF (≥1). Conclusion: This study revealed that research activity in KSA is increasing. However, there is an increasing trend of publishing in local journals with a low IF. More effort is required to promote medical research in Saudi Arabia.